Government-Industry Policy on Inventory Management Technology for Enhanced Productivity and GDP Growth Rate in Nigeria - Benedict Ejikeme, Odigbo; Nneka, Maduagwu; Uduak Udo, Sunday (British Journal of Marketing Studies, 2016)
Today’s development is not possible without advanced technology. In the area of manufacturing, technology is quickly changing the way in which stock is handled and controlled for enhanced productivity. Sophisticated information gathering systems can track items from the purchase order to the final customer on the sales chain. Automation can dramatically impact all phases of inventory management, including counting, monitoring, recording and retrieval of items, storage location; recording changes to inventory; and anticipating inventory needs, including inventory handling requirements. The manufacturing and retail industries, worldwide, have created standards to take advantage of new technologies and computerized systems such as the Radio Frequency Identification (RFID), barcodes, vending machines, warehouse technology management system, etc. All these provide accurate inventory information on a constant basis thus, enhance organisation’s productivity and increase its competitive edge over companies that are slow to take advantage of these new technologies. Finding the position of Nigerian manufacturing firms in this equation was the major focus of the study. Results indicated poor performance. Based on that, a case for government-industry policy framework that will make it mandatory for manufacturers in Nigeria to use technology-based inventory management system for enhanced productivity and GDP growth was made by the authors.